Phase evolution and thermophysical properties of high‐entropy RE2(Y0.2Yb0.2Nb0.2Ta0.2Ce0.2)2O7 oxides. Issue 8 (26th April 2022) - Xu, Liang; Su, Lei; Wang, Hongjie; Niu, Min; Zhuang, Lei; Peng, Kang; Fan, Xingyu; Gao, Hongfei; Lu, De
Abstract: Pursuing novel thermal barrier–coating materials with lower thermal conductivity and high‐temperature stability can simultaneously improve the working efficiency and service temperature of a gas turbine. In this study, a series of high‐entropy RE2 (Y0.2 Yb0.2 Nb0.2 Ta0.2 Ce0.2 )2 O7 (RE = La, Nd, Sm, Gd, Dy, and Er) oxides were prepared though solid‐state reaction. Through tuning the rare‐earth cations, an order–disorder transition occurs from certain partially ordered weberite structure ( C 2221 ) to disordered defective fluorite structure ( Fm 3 ¯ 3 m ). All the high‐entropy RE2 (Y0.2 Yb0.2 Nb0.2 Ta0.2 Ce0.2 )2 O7 oxides possess low thermal conductivity in the range of 0.91–1.34 W m −1 K −1 at room temperature, which can be attributed to increased lattice anharmonicity and disorder, resulting in additional phonon scattering. Herein, we proved that the incorporation of heterovalent cations at B‐sites in high‐entropy A2 B2 O7 crystals is an effective strategy to reduce the thermal conductivity without compromising the decrease of oxygen vacancy. Moreover, the high‐entropy RE2 (Y0.2 Yb0.2 Nb0.2 Ta0.2 Ce0.2 )2 O7 oxides show the relatively higher thermal expansion coefficients of 10.3–10.7 × 10 −6 °C −1 and excellent phase stability at elevated temperatures.